The Impact of Female Diectors on Dividend Policy - Maftucho, Wiwit Nur; Khoiruddin, Moh. (Universitas Negeri Semarang, 2018)
The purpose of this study is to explain whether there is any effect of female directors towards dividend policy in developing countries, and whether state ownership moderates the effect of female directors towards dividend policy in developing countries. The population in this study is a non-financial company listed on the Indonesia Stock Exchange and Malaysia stock exchange on the period 2011-2015. The number of samples is 145 data for companies in Indonesia Stock Exchange and 1145 data for companies in Malaysia stock exchange by using purposive sampling method. The dividend payment variables are proxied by the Dividend Payout Ratio (DPR) and Dividend Yield (YIELD), female directors is proxied by the percentage of female directors, the state ownership is proxied by the percentage of share ownership by the government. Censored regression analysis using Eviews9 is used for data analysis. Based on the regression model used, it is found that there is effect of female directors on dividend policy in Indonesia, whereas there is no effect of female directors on dividend policy in Malaysia. However, positive state ownership moderates the effect female directors towards dividend policyt at companies in Malaysia.